EFEKTIVITAS EKSTRAK DAUN BINAHONG (ANREDERA CORDIFOLIA) TERHADAP PENGHAMBATAN PERTUMBUHAN BAKTERI SHIGELLA FLEXNERI DENGAN METODE SUMURAN - AINURROCHMAH, ANIS (LenteraBio: Berkala Ilmiah Biologi, 2013)
Shigella flexneri is one of pathogenic bacteria that cause dysentery. Disease caused by Shigella sp. can be cured using antibiotics, but the excessive use of antibiotics causes bacterial resistance. One of antibiotics alternate is secondary metabolites of binahong (Anredera cordifolia) leaves. This research aimed to determine the growth inhibitory of S. flexneri strain BW 1201 and the optimal concentration of binahong leaf extracts to inhibit the growth of S. flexneri strain BW 1201. Binahong leaves extracts was prepared by maceration method, using 96% ethanol. The filtrate of binahong leaves was evaporated by vacuum rotary evaporator to obtain a viscous extract. Binahong leaf extracts tested concentration were 0% (distilled water/control), 40%, 60%, 80% dan 100% with 4 repetitions. Data obtained were the diameter of clear zone (mm) formed in the culture medium of S. flexneri strain BW 1201. Data were analyzed using one way variant analysis test and Duncan's test. Results showed that the binahong leaves extracts had inhibitory effects on the growth of S. flexneri strain BW 1201 and optimal clear zone of 27,2 mm against the test bacterial at the concentration of 100%.   Key words: Shigella flexneri; binahong leaf extracts; growth inhibitory of bacterial; well difussion method